Pembentukan Lembaga Pengawas Pelindungan Data Pribadi dalam Perspektif Pembentukan Lembaga Negara Baru (Establishment of a Personal Data Protection Supervisory Agency in the Perspective of the Establishment of a New State Institution) - Denico Doly (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2021)
The rules for protecting personal data are spread across various laws and regulations. This causes sectoral supervision over the implementation of personal data protection, with the government has not optimally protected public personal data, and the institutions responsible for protecting personal data are also not yet integrated in nature. This article examines the urgency of establishing a personal data protection supervisory agency and what the ideal form of the institution is. This paper aims to examine the urgency and ideal form of a personal data protection supervisory agency. In writing the article which uses a normative juridical approach and is analyzed qualitatively, it is stated that the urgency of establishing a personal data protection institution, are namely, first, to ensure that the rules for protecting personal data are implemented; second, there are countries who have established personal data protection supervisory agencies; third, supervision and law enforcement of personal data protection is currently still insubstantial; fourth, the high number of legal subjects of personal data protection; fifth, there are multiple personal data controllers or processors; and sixth, there is still a lack of public awareness on personal data protection. The ideal form of a personal data protection supervisory agency should be an independent state institution that is formed by law and is an auxiliary state’s organ, which has the functions, duties, and authorities regulated by law. The establishment of this personal data protection supervisory agency needs to be regulated in the Personal Data Protection Law. AbstrakAturan pelindungan data pribadi tersebar di berbagai peraturan perundang-undangan. Hal ini menyebabkan pengawasan atas pelaksanaan pelindungan data pribadi bersifat sektoral, pemerintah belum optimal melakukan pelindungan data pribadi masyarakat, dan lembaga yang bertanggung jawab untuk melindungi data pribadi juga masih belum terintegrasi. Artikel ini mengkaji urgensi pembentukan lembaga pengawas pelindungan data pribadi dan bagaimana bentuk ideal lembaga tersebut. Tulisan ini bertujuan untuk mengkaji urgensi dan bentuk ideal lembaga pengawas pelindungan data pribadi. Dalam penulisan artikel yang menggunakan metode pendekatan yuridis normatif dan dianalisis secara kualitatif, disebutkan urgensi pembentukan lembaga pelindungan data pribadi, yaitu kesatu, untuk memastikan aturan pelindungan data pribadi diimplementasikan; kedua berbagai negara membentuk lembaga pengawas pelindungan data pribadi; ketiga, pengawasan dan penegakan hukum pelindungan data pribadi saat ini masih lemah; keempat, banyaknya subjek hukum pelindungan data pribadi; kelima, pengendali atau prosesor data pribadi yang banyak; dan keenam, masih kurangnya kesadaran masyarakat akan pelindungan data pribadi. Bentuk ideal lembaga pengawas pelindungan data pribadi sebaiknya berupa lembaga negara independen yang dibentuk dengan undang-undang dan bersifat auxalari state’s organ, yang memiliki fungsi, tugas, dan kewenangan yang diatur dalam undang-undang. Pembentukan lembaga pengawaspelindungan data pribadi ini perlu diatur dalam UU Pelindungan Data Pribadi.